A Look Back at Modern Finance: Accomplishments and Limitations. Issue 4 (December 2016) - Fama, Eugene F.; Stern, Joel M.
Abstract : In a conversation held in June 2016 between Nobel laureate Eugene Fama of the University of Chicago and Joel Stern, chairman and CEO of Stern Value Management, Professor Fama revisited some of the landmarks of "modern finance, " a movement that was launched in the early 1960s at Chicago and other leading business schools, and that gave rise to Efficient Markets Theory, the Modigliani‐Miller "irrelevance" propositions, and the Capital Asset Pricing Model. These concepts and models are still taught at prestigious business schools, whose graduates continue to make use of them in corporations and investment firms throughout the world. But while acknowledging the staying power of "modern finance, " Fama also notes that, even after a half‐century of research and refinements, most asset‐pricing models have failed empirically. Estimating something as apparently simple as the cost of capital remains fraught with difficulty. He dismisses betas for individual stocks as "garbage, " and even industry betas are said to be unstable, "too dynamic through time." What's more, the wide range of estimates for the market risk premium—anywhere from 2% to 10%—casts doubt on their reliability and practical usefulness. And as if to reaffirm the fundamental insight of the M&M "irrelevance" propositions—namely, that what companies do with the right‐hand sides of their balance sheets "doesn't matter"—Fama observes that "we still have no real resolution on the key questions of debt and taxes, or dividends and taxes." But if he has reservations about much of modern finance, Professor Fama is even more skeptical about subfields now in vogue such as behavioral finance, which he describes as "mostly just dredging for anomalies, " with no underlying theory and no testable predictions. Although he does not dispute that a number of well‐documented traits from cognitive psychology show up in individual behavior, Fama says that behavioral economists have thus far failed to come up with a testable theory that links cognitive psychology to market prices. And he continues to defend the concept of "efficient markets" with which his name has long been closely associated, while noting that empirically based asset pricing models such as his (with Ken French) "three‐factor" CAPM have produced much better results than the standard CAPM.